DEVELOPMENT OF MULTI CRITERIA APPROACH AND GRAPHICAL USER INTERFACE FOR LOW EMBODIED ENERGY BUILDINGS - HARUNA, ABDULRAHMAN (2021)
Construction industry have been widely seen to have negative environmental impacts and is a main user of a large variety of natural and synthesized materials.